Further validation of magnifying chromocolonoscopy for differentiating colorectal neoplastic polyps in a health screening center (2007)
The accuracy of conventional colonoscopy to differentiate neoplastic and non‐neoplastic polyps is limited, justifying a biopsy for histologic analysis. Magnifying chromocolonoscopy has emerged as the best tool available for differentiating adenomatous and hyperplastic polyps during colonoscopy; however, magnifying endoscopes are rarely used in endoscopy units. This study aimed to further validate the effectiveness of magnifying chromocolonoscopy in the diagnosis of neoplastic colorectal polyps in a screening center. Five hundred average‐risk subjects were randomly divided into two groups: a magnifying chromocolonoscopy group and a conventional chromocolonoscopy group, each of 250 subjects. Lesions were analyzed according to Kudo's classification of pit pattern (types I–V) and additionally subdivided into non‐neoplastic (types I–II) and neoplastic (types III–V). Lesions judged as neoplastic were resected and those judged as non‐neoplastic were left in situ. Only lesions ≤10 mm were included in the study. Resected lesions were analyzed with histopathological examination. The overall accuracy of magnifying chromocolonoscopy for differentiating neoplastic lesions (95%, 135 of 142), was significantly higher than that of conventional chromocolonoscopy (84%, 102 of 122; P < 0.01). The accuracy of magnifying chromocolonoscopy for differentiating neoplastic lesions ≤5 mm was 94% (135 of 142), whereas that of conventional chromocolonoscopy was only 78% (69 of 89; P < 0.001). Results were not affected by the macroscopic types. Magnifying chromocolonoscopy is superior to conventional chromocolonoscopy for the diagnosis of colorectal neoplastic lesions in the setting of a health testing center.